1994
DOI: 10.1902/jop.1994.65.12.1107
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Clinical Evaluation of the Subpedicle Connective Tissue Graft for the Coverage of Gingival Recession

Abstract: The purpose of this study was to clinically evaluate the 1-year coverage of gingival recessions by a subpedicle connective tissue graft according to the original technique compared to untreated recessions by measuring probing sulcus depth (PSD), height of keratinized tissue (HKT), and mucogingival junction location changes. Paired gingival recessions were selected in 15 patients. In each patient, one recession was randomly assigned for treatment (test group) and the other recession was left untreated (control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 19 publications
2
51
0
4
Order By: Relevance
“…4 The predictability of the multiple surgical variants of subepithelial connective tissue grafts (SCTGs) and the mucogingival changes associated with these procedures following treatment of human gingival recessions have been documented in numerous studies. [5][6][7][8][9][10][11][12][13][14][15][16][17] Various clinical investigations reported an increase in gingival width following treatment of recession defects with subepithelial connective tissue graft combined with coronally positioned flaps. [10][11][12][13][14][15][16][17] However, no attempt has been made in these studies to justify this increase in gingival width or correlate the increase to surgical parameters.…”
mentioning
confidence: 99%
“…4 The predictability of the multiple surgical variants of subepithelial connective tissue grafts (SCTGs) and the mucogingival changes associated with these procedures following treatment of human gingival recessions have been documented in numerous studies. [5][6][7][8][9][10][11][12][13][14][15][16][17] Various clinical investigations reported an increase in gingival width following treatment of recession defects with subepithelial connective tissue graft combined with coronally positioned flaps. [10][11][12][13][14][15][16][17] However, no attempt has been made in these studies to justify this increase in gingival width or correlate the increase to surgical parameters.…”
mentioning
confidence: 99%
“…In many cases, more than one procedure is necessary to treat gingival recession. Consequently, the combination of two or more procedures has been increasingly used to provide successful results 5,19,21) . According to the literature, many factors influence the level of success of each procedure, among which interproximal bone level and selection of the most adequate technique for a particular case are the most important 11) .…”
Section: Discussionmentioning
confidence: 99%
“…Root coverage averaged for 43% for the free gingival graft group, and 80% for the connective tissue graft group. Borghetti and Louise, 34 in their split-mouth controlled clinical study, reported a 70% success rate of root coverage 1 year postoperatively.…”
Section: Connective Tissue Autogenous Graftsmentioning
confidence: 97%